2019
DOI: 10.1177/0333102419829007
|View full text |Cite
|
Sign up to set email alerts
|

Safety and tolerability of calcitonin-gene-related peptide binding monoclonal antibodies for the prevention of episodic migraine – a meta-analysis of randomized controlled trials

Abstract: Aim To systematically evaluate the safety and tolerability of calcitonin-gene-related peptide binding monoclonal antibodies from the results of randomized controlled trials. Methods Online databases were searched on calcitonin-gene-related peptide binding monoclonal antibodies for the prevention of episodic migraine. Overall withdrawal, withdrawal due to adverse events, adverse events, serious adverse events and specific adverse events were extracted from the included studies. A meta-analysis was performed wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 27 publications
2
41
0
2
Order By: Relevance
“…A recent meta-analysis of randomized controlled trials of CGRP monoclonal antibodies for the prevention of episodic migraine supported the findings of safety and tolerability of CGRP monoclonal antibodies [25]. The meta-analysis included ten phase 2 and phase 3 clinical trials; four of those trials were galcanezumab studies.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…A recent meta-analysis of randomized controlled trials of CGRP monoclonal antibodies for the prevention of episodic migraine supported the findings of safety and tolerability of CGRP monoclonal antibodies [25]. The meta-analysis included ten phase 2 and phase 3 clinical trials; four of those trials were galcanezumab studies.…”
Section: Introductionmentioning
confidence: 84%
“…For diastolic blood pressure: treatment-emergent low ≤50 mmHg with ≥10 mmHg decrease; treatment-emergent high ≥90 mmHg with ≥10 mmHg increase; PCS high ≥105 mmHg with ≥15 mmHg increase; sustained elevation ≥90 mmHg with ≥10 mmHg increase for 2 consecutive office visits c For pulse: treatment-emergent low < 50 bpm with ≥15 bpm decrease; treatment-emergent high > 100 bpm with ≥15 bpm increase; sustained elevation > 100 bpm with ≥15 bpm increase for 2 consecutive office visits A meta-analysis of 10 randomized controlled trials of CGRP monoclonal antibodies for the prevention of episodic migraine was recently published [25]. This analysis supports the findings that CGRP monoclonal antibodies are generally safe and well tolerated.…”
Section: Discussionmentioning
confidence: 99%
“…This model is based upon the distribution of the neuropeptide calcitonin-gene-related-peptide (CGRP), which has a complex distribution within the vestibular periphery (74). One must acknowledge that the use of CGRP-binding monoclonal antibodies as biologics in the clinical practice of migraine management (75,76) has a potential to produce a side effect of peripheral vestibular dysfunction or injury due to the impairment of vestibular efferent function.…”
Section: Migraine Headache and Outcomes After Round Window Reinforcementmentioning
confidence: 99%
“…Systemic reviews have confirmed the effectiveness and safety of CGRP monoclonal antibodies for the treatment of migraine and cluster headache [21,22]. However, until now, no study is conducted to systemically analyze the efficacy and safety profiles of galcanezumab across different doses, therefore, we conducted a meta-analysis to evaluate the dose-related efficacy and tolerability of galcanezumab for the treatment of migraine and cluster headache.…”
Section: Introductionmentioning
confidence: 99%